2013
DOI: 10.1007/s00223-013-9731-9
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Osteoporosis and Hypertension: The Role of A Low Dairy Intake

Abstract: Hypertension and related cardiovascular diseases are reported to be associated with osteoporosis. A nutritional pathway related to dairy intake has been postulated for both diseases. The aim of this study was to assess calcium intake from dairy sources as a possible pathogenic link between osteoporosis and hypertension. This was a cross-sectional observational study performed on 3,301 postmenopausal women referred for a densitometry screening. Osteoporosis was diagnosed by lumbar dual-energy X-ray absorptiomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…In view of the previous epidemiologic evidence that low dietary calcium intake significantly increases blood pressure 9,16,17 , this result could be understood as an effect of calcium homeostasis: theoretically a negative calcium balance could affect osteoporosis, hypertension and the otolith environment responsible for BPPV. An association between osteoporosis and hypertension was previously reported in postmenopausal women 18 . Those authors suggested that low dairy calcium intake might increase the risk of both diseases, acting as a possible pathogenic link 18 .…”
Section: Discussionmentioning
confidence: 74%
“…In view of the previous epidemiologic evidence that low dietary calcium intake significantly increases blood pressure 9,16,17 , this result could be understood as an effect of calcium homeostasis: theoretically a negative calcium balance could affect osteoporosis, hypertension and the otolith environment responsible for BPPV. An association between osteoporosis and hypertension was previously reported in postmenopausal women 18 . Those authors suggested that low dairy calcium intake might increase the risk of both diseases, acting as a possible pathogenic link 18 .…”
Section: Discussionmentioning
confidence: 74%
“…Several meta-analyses of randomised controlled trials have also indicated that Ca supplementation can lead to a small reduction in systolic and diastolic blood pressure; therefore, Ca supplements might be beneficial in patients with hypertension (125,126) . Varenna et al (127) have confirmed an association between hypertension and osteoporosis. There is a higher prevalence of hypertension in women with osteoporosis and a higher prevalence of osteoporosis in women with hypertension.…”
Section: Dietary Calciummentioning
confidence: 91%
“…16 BMD was measured for all subjects at the proximal femur and lumbar spine (L1-L4) with a coefficient of variation of 0.8% and < 1.2%, respectively. It was expressed in g/cm 2 and as peak bone mass percentage in normal subjects (T-score). BMD results for the femoral neck and lumbar spine were classified into 3 groups according to World Health Organization criteria: normal (T-score > −1.0 SD), OP (T-score −1.0 to −2.5 SD) and OS (T-score < −2.5 SD).…”
Section: Measurement Of Body Composition By Dual-energy X-ray Absorptmentioning
confidence: 99%